The EXPERIMENTAL STUDY OF COLD-FORMED STEEL CLOSED BOX SECTION 32 MM X 31 MM X 0,3 MM BEAM ON 4-POINT FLEXURAL LOADING - Pregawati, Dyah Ayu; Purnomo, Heru (Construction and Material Journal, 2025)
This study evaluates the effect of beam length and fold position on the flexural performance, deflection, and failure pattern of closed-box cold-formed steel beams with dimensions of 32 mm × 31 mm × 0.3 mm under four-point bending tests. A total of 18 specimens were tested using this method with two length variations, 500 mm and 1100 mm, and fold positions located either on the top flange, bottom flange, or side web. The results show that the 500 mm beams were able to carry greater vertical loads compared to the 1100 mm beams, with smaller mid-span deflections and relatively smaller rotation. In contrast, the 1100 mm beams experienced more significant mid-span deflections and rotations. The presence of folds on the top or bottom flanges increased the beam’s vertical load-carrying capacity by approximately 10% to 15% compared to when the fold was placed on the side web. The failure pattern of the shorter beams was dominated by excessive deformation on the upper part of the beam due to vertical loading, and similar deformation was also observed in the longer beams. This excessive deformation occurred beneath the vertical load application point near the roller support. In addition, comparison with the Direct Strength Method (DSM) revealed that DSM predicted higher flexural moment capacities than those obtained from experiments, M experiment / MDSM ratios ranging from 0.33–0.45 for 500 mm spans and 0.49–0.54 for 1100 mm spans. These results indicate that DSM is more conservative for shorter beams and can serve as a safe preliminary approach for designing cold-formed steel beams subjected to four-point bending.